Pengaruh Pelatihan dan Kompensasi Terhadap Kinerja Karyawan di PT. Maan Ghodaqo Shiddiq Lestari Jombang - Eky Nikmatul Rizki (BIMA : Journal of Business and Innovation Management, 2018)
Improving quality of Human Resources in the company is one way to survive with global developments and competitive competition between companies. Training and Compensation are important things for companies, especially PT. Maan Ghodaqo Shiddiq Lestari which improve performance effectively and efficiently and improve employee’s welfare.PT.Maan Ghodaqo Shiddiq Lestari is a company engaged in food that produces mineral water with the brand name is “MAAQO”. This study aims analyze the effect of trainning and compensation on employee’s performance. This study is quantitative. The population is 75 employee’s. The sample technique used is saturated samples.The results of this study that (1) trainning variabels partially has a positive and significant effect on performance. Which t hitung is 3,532 and the significant is 0,001. (2) compensation partialy has a positive and significant effect on performance. Which t hitung 2,381 and the significant is 0,020. (3) Trainning adn Compensation variabels simultaneously have a positive effect on employee’s performance. Which F hitung is 13,852 and significant is 0,000.